An orally administered gold nanocluster with ROS scavenging for inflammatory bowel disease treatment - Fei Wang; Qianhui Li; Tingting Xu; Zhu Li; Yongxin Jiang; Yan Ma; Xiaohu Li; Wanni Wang; Haisheng Qian (Fundamental Research)
Oxidative stress that is induced by excessive reactive oxygen species (ROS) is considered to be a key pathophysiological mechanism of inflammatory bowel disease (IBD), and restoring redox homeostasis in the inflammatory region by eliminating ROS is an effective way to treat IBD. Herein, ultrasmall Au25 nanoclusters (Au25 NCs) were synthesized using a simple improved protocol, which has good physiological stability and biosafety and can be noninvasively monitored by clinical computed tomography (CT) after oral administration. Au25 NCs can eliminate ROS such as ABTS radicals, superoxide free radicals (•O2−), and hydroxyl free radicals (•OH), upregulate the expression level of antioxidant enzymes, inhibit the expression of proinflammatory cytokines, and finally interrupt the inflammatory circuit of IBD to achieve the effective prevention and delayed treatment of IBD. This work will demonstrate the protective effect of Au25 NCs on IBD in living animals, which suggests a new nanomedicine strategy for IBD treatment.